Value of Procollagen Type I Aminoterminal Propeptide in Women with Breast Cancer with regard to Metastases - Clouth, A. (SAGE-Hindawi Access to Research, 2011)
Background. The aim of this study was to show the importance of the bone marker procollagen type 1 aminoterminal propeptide (P1NP) in detecting bone metastases in women suffering from breast cancer. We furthermore investigated to what degree P1NP is correlated to the degree of bone metastases, and if P1NP is increased in patients with metastases other than bone. Patients and Methods. We analyzed 80 serum samples of women (17 premenopausal/63 postmenopausal) with breast cancer. Therefore we used a specific immunoassay “ELECSYS 2010” by Roche Diagnostics. We divided our group of patients with regard to menopausal status, sites of metastases and number of bone metastases. Results. As a result we found higher concentrations of P1NP in women with radiologically confirmed bone metastases (median: 125.75 ng/mL) in comparison to the collective without bone involvement (median: 73.61 ng/mL). However, both groups showed values above the applied cutoff values of median 27.8 ng/mL for premenopausal women and median: 37.1 ng/mL for the postmenopausal group due to the fact that all patients had cancer. Furthermore higher P1NP concentrations were found in women with more than 5 sites of bone metastases (median: 183.9 ng/mL) than in patients with only one site of bone metastases (median: 37 ng/mL). Also patients with no bone involvement but other sites of metastases showed quite high P1NP concentrations (median: 73.61 ng/mL). Conclusion. The marker of bone turnover procollagen type 1 aminoterminal propeptide can be considered as a useful tool for estimating the extent of bone involvement and for the detection of bone metastases. P1NP cannot replace conventional methods for detecting bone metastases such as radiological methods but it can help clarify unclear radiological results. This study does not take into account the change of P1NP concentration during the course of therapy.